Development of MATLAB radar toolbox - Han, Aiguo (2012)
RAdio Detection And Ranging (Radar) is a method of using electromagnetic waves to remote-sense the position, velocity, and identifying characteristics of targets. Radar has wide range of military and civilian applications. Typical uses include but not limited to air-defense system, air traffic control, weather forecast and ground imaging for geological observations.